2014
DOI: 10.1103/physreva.90.062510
|View full text |Cite
|
Sign up to set email alerts
|

Quantum beat spectroscopy: Stimulated emission probe of hyperfine quantum beats in the atomic Cs8p2P3/2level

Abstract: Measurements of hyperfine polarization quantum beats are used to determine the magnetic dipole (A) and electric quadrupole (B) coupling constants in the excited atomic Cs 8p 2 P 3/2 level. The experimental approach is a combination of pulsed optical pumping and time-delayed stimulated-emission probing of the excited level. From the measured evolution of the atomic linear polarization degree as a function of probe delay time, we determine the hyperfine coupling constants A = 7.42(6) MHz and B = 0.14(29) MHz.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…At t = 1.5 ns the linear polarization for the 6s 2 S 1/2 → 8p 2 P 3/2 → 5d 2 D 5/2 transition is obtained to be 12.4(5)%. This measurement is in excellent agreement with theory [23,24]. Figure 3 illustrates typical fluorescence signal immediately after stimulated emission pump laser arrives into the interaction region.…”
Section: Experimental Approach To Measure Polarization Spectrasupporting
confidence: 87%
See 1 more Smart Citation
“…At t = 1.5 ns the linear polarization for the 6s 2 S 1/2 → 8p 2 P 3/2 → 5d 2 D 5/2 transition is obtained to be 12.4(5)%. This measurement is in excellent agreement with theory [23,24]. Figure 3 illustrates typical fluorescence signal immediately after stimulated emission pump laser arrives into the interaction region.…”
Section: Experimental Approach To Measure Polarization Spectrasupporting
confidence: 87%
“…The linear polarization degree evolves in time due to hyperfine structure in the excited level. We have measured the time evolution of polarization from t = 0 to t = 150 ns in our earlier work [23]. At t = 1.5 ns the linear polarization for the 6s 2 S 1/2 → 8p 2 P 3/2 → 5d 2 D 5/2 transition is obtained to be 12.4(5)%.…”
Section: Experimental Approach To Measure Polarization Spectramentioning
confidence: 96%
“…[52] and [53]; less so with those of Refs. [54][55][56]. The uncertainty of our measurement is comparable to, but slightly larger than that of Refs.…”
Section: Resultssupporting
confidence: 51%
“…Furthermore, it is shown that polarization configuration can be chosen to distinguish between the dynamics of the preparation stage and the selection rules of the electric quadrupole transition. This could be a useful toolbox beyond the dipole approximation, for example in the study of polarization degree in optical transitions as made by Baumgartner et al [13] and in the study of quantum beat spectroscopy made by Bayram et al [14].…”
Section: Introductionmentioning
confidence: 99%